Senolytic elimination of Cox2-expressing senescent cells inhibits the growth of premalignant pancreatic lesions. Issue 2 (1st March 2021) - Kolodkin-Gal, Dror; Roitman, Lior; Ovadya, Yossi; Azazmeh, Narmen; Assouline, Benjamin; Schlesinger, Yehuda; Kalifa, Rachel; Horwitz, Shaul; Khalatnik, Yonatan; Hochner-Ger, Anna; Imam, Ashraf; Demma, Jonathan Abraham; et al.
Abstract : Objective: Cellular senescence limits tumourigenesis by blocking the proliferation of premalignant cells. Additionally, however, senescent cells can exert paracrine effects influencing tumour growth. Senescent cells are present in premalignant pancreatic intraepithelial neoplasia (PanIN) lesions, yet their effects on the disease are poorly characterised. It is currently unknown whether senolytic drugs, aimed at eliminating senescent cells from lesions, could be beneficial in blocking tumour development. Design: To uncover the functions of senescent cells and their potential contribution to early pancreatic tumourigenesis, we isolated and characterised senescent cells from PanINs formed in a Kras-driven mouse model, and tested the consequences of their targeted elimination through senolytic treatment. Results: We found that senescent PanIN cells exert a tumour-promoting effect through expression of a proinflammatory signature that includes high Cox2 levels. Senolytic treatment with the Bcl2-family inhibitor ABT-737 eliminated Cox2-expressing senescent cells, and an intermittent short-duration treatment course dramatically reduced PanIN development and progression to pancreatic ductal adenocarcinoma. Conclusions: These findings reveal that senescent PanIN cells support tumour growth and progression, and provide a first indication that elimination of senescent cells may be effective as preventive therapy for the progression of precancerous lesions.